Investigating the effect of governance on unemployment: A case of South Asian countries - Aiza Shabbir; Shazia Kousar; Farzana Kousar; Amna Adeel; Rana Adeel Jafar (International Journal of Management and Economics, 2019)
This study aims to investigate the short-run and long-run relationship between economic variables and the unemployment rate in South Asian countries. A panel vector error correction model is used to establish the long-run and the short-run relationship between the unemployment rate and the selected economic variables. Data were collected from WDI, WGI, and FDSD for the years 1994-2016. In order to determine the direction of the relationship, the Granger causality test was used. Impulse response functions (IRFs) and forecast error variance decomposition were used to assess the stability of the relationship between the unemployment rate and economic variables over time. The finding of the study showed a negative and significant relationship at the 5% level of significance between governance, internet users, mobile cellular subscriptions, fixed broadband subscriptions, and human capital and the unemployment rate of South Asian economies. On the other hand, financial activity (credit) and population growth had a positive and significant relationship with the unemployment rate. Finally, the Granger causality test showed bidirectional causality between governance and unemployment rate, while internet users and fixed broadband subscriptions showed unidirectional causality with the unemployment rate; furthermore, population growth, financial activity (credit), mobile cellular subscriptions, and human capital showed no causality in the short run.
Keywords: E24; J64; 000; 011; E02; 650; economic variables; unemployment; VECM; South Asian countries; governance; ICT